"Alignment-Plus": alignment with schooling requirements and cultural-bridging among indigenous middle-class parents. Issue 1 (2nd January 2020) - Milne, Emily; Wotherspoon, Terry
Abstract: Education research demonstrates that positive and trusting family/school relationships support academic achievement but for many Indigenous parents in Canada legacies of residential schooling have made it difficult to develop strong bonds with schools and teachers. Drawing on interviews with 69 Indigenous parents and eight non-Indigenous parents of children who identify as Indigenous from two Canadian provinces, this study explores the intersection between family/school relationships and social class, and highlights distinct ways that middle-class Indigenous parents are involved in schooling. Shifting from a "deficit" approach to a "strength based" approach highlights existing resources and capacities among those who are comfortable and familiar with navigating the education system while also creating prospects to build on that capacity to empower others who are less familiar/comfortable.